Prevalence, determinants, and association of overweight/obesity with non-communicable disease-related biomedical indicators: A cross-sectional study in schoolteachers in Kabul, Afghanistan - Sharifullah Alemi; Keiko Nakamura; Ahmad Shekib Arab; Mohammad Omar Mashal; Yuri Tashiro; Kaoruko Seino; Shafiqullah Hemat (Public Library of Science (PLoS), 2023)
Overweight/obesity constitutes a major risk factor for non-communicable diseases (NCDs), whose global prevalence is growing rapidly, including in Afghanistan. However, the effects of risk factors on NCDs have rarely been studied in the educator workforce. Therefore, the objective of this study is to determine the prevalence, determinants, and association of overweight/obesity with NCD-related biomedical indicators among schoolteachers in Afghanistan. The sample comprised 600 schoolteachers aged 18 years and above. We conducted questionnaire interviews, anthropometric measurements, and blood biochemistry tests. The main explanatory variable was overweight/obesity (body mass index ≥ 25.0 kg/m2). NCD-related biomedical indicators were the outcome variables. Poisson regression models were applied to investigate the association between overweight/obesity and outcome variables. The prevalence of overweight/obesity was 58.2%, which was significantly higher in women, those aged 41-50 years, married participants, and those with 10-20 years of working experience than in their counterparts. After adjusting for sociodemographic variables and lifestyle behaviors, overweight/obesity was significantly associated with hypertension (adjusted prevalence ratio [aPR] = 1.83, 95% confidence interval [CI]: 1.33-2.51); elevated levels of glycosylated hemoglobin (HbA1c) (aPR = 1.35, 95% CI: 1.01-1.79), total cholesterol (aPR = 1.67, 95% CI:1.14-2.44), low-density lipoprotein cholesterol (LDL-C) (aPR = 1.29, 95% CI: 1.10-1.50), and triglycerides (aPR = 1.98, 95% CI: 1.57-2.50), and having three or more comorbidities (aPR = 1.90, 95% CI: 1.47-2.47). Our findings demonstrated a high prevalence of overweight/obesity among schoolteachers. In addition, we found significant associations of overweight/obesity with a higher prevalence of hypertension; elevated serum levels of HbA1c, total cholesterol, LDL-C, and triglycerides; and comorbid conditions in schoolteachers. The findings highlight the need for worksite interventions that promote weight control among schoolteachers with overweight/obesity to reduce the burden of NCDs.